The system of 13-moment approximate equations the rarefied gas aerodynamics - Skakauskas, V. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. И. Скакаускас. Тринадцатимоментная система приближенных уравнений аэромеханики разреженных газов V. Skakauskas. Praretintų dujų aeromechanikos 13 momentų artutinių lygčių sistema